Policy Formulation and Adoption of Revised Islamic Education Curriculum as stated in the Decree of Religion's Ministry (KMA) Number 183 of 2019 - Omay Komarudin; Qiqi Yulianti Zakiyah; Supiana Supiana (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
The stages in making the education policy process by Formulation and Adoption process. The policy formulation is intended for the best problem solving derived from various alternatives or existing policy options. The problem of revision of the Islamic Education curriculum is one of the solutions for handling radicalism in Islamic Religion Education (IRE) curriculum from several policy options including the elimination of jihad and caliphate material, changing subjects, transferring caliphate material to subjects of Islamic cultural history, while Jihad material is more directed towards a seriousness to do best activities. After choosing the best policy, it needs to be legitimized so that the decision is well received because it is in accordance with the procedures applicable to the general public and political or moral values. The policy for revising the IRE curriculum is contained in Decision of Religion Ministry no 183/2019 and endorsed by the Ministry of Religion in the field of Islamic Education, so that it becomes the best guideline in national and state life by maintaining national security stability.